Improving Hole Transport and Extraction by Interface Engineering in Perovskite Solar Cells. Issue 4 (9th February 2022) - Li, Lingfeng; Wei, Qianwen; Yu, Leiming; Wang, Juan; Wang, Rongfei; Sun, Tao; Wang, Chong; Yang, Yu; Wen, Xiaoming
Abstract : Efficient carrier transport and extraction is essentially important for perovskite solar cells (PSCs). Here, an outstanding organic material tetraphenyldibenzoperiflanthene (DBP) is used to modify the perovskite/spiro‐OMeTAD interface as the intermediate layer. Using time‐resolved photoluminescence technique and dynamic analysis of photogenerated charge carriers, a significantly faster hole extraction and faster hole transport occurring in perovskite/DBP/spiro interface is demonstrated, this is ascribed to an intermixing layer of perovskite and thin DBP layer. The improved mobility has been further confirmed by the Hall measurement. As a consequence, the improved hole extraction and reduced interface recombination result in an improved performance of PSC, including improved conversion efficiency, mitigated J–V hysteresis, and amelioration of stability under humid conditions. This work provides a detailed insight into the transport and extraction of charge carriers improved by the intermediate layer of organic small molecules as an effective strategy for interface engineering by solution spin coating. Abstract : Significantly improved perovskite solar cell is demonstrated by spin‐coating an ultrathin tetraphenyldibenzoperiflanthene layer between perovskite and Spiro‐OMeTAD. Dynamic analysis of photogenerated carriers by time‐resolved photoluminescence reveals the intermediate layer leads to faster hole transport and hole extraction due to smoothing the energy alignment and passivation in the interface, this eventually achieves a much improved conversion efficiency and stability.